Populism and Anti-Intellectualism: the Evolution of the Political Views of the Italian "Five Star Movement" (2005–2022) - Vakhrushev, Ivan Iurevich (Исторический журнал: научные исследования, 2024)
Among the characterizing features of populism, which has become an integral part of the party-political systems of Western countries, anti-intellectualism is often listed. It is understood as distrust of intellectuals, expert knowledge and the scientific community. Italy, the “political laboratory of Europe,” provides rich material for studying the connection between anti-intellectualism and populism. This article attempts to analyze the role and evolution of anti-intellectualism in populist discourse using the example of the Italian Five Star Movement (M5S). Five Stars, founded by comedian Beppe Grillo and IT entrepreneur Gianroberto Casaleggio, has become one of the main parties in the country, while expressing controversial views from the point of view of the scientific community. Using qualitative text and discourse analysis, the party's official blogs, M5S bills, articles from Italian and foreign media are analyzed. As a result, this work offers a balanced view of the gradual development of anti-intellectual sentiments within the Movement in the context of the overall process of institutionalization of the party into the mainstream of Italian politics during the period of 2005–2022. The subject of this article remains completely unexplored in Russian scientific literature and little studied in foreign science. Analysis of this subject shows that in the process of institutionalization, the long stay of the anti-establishment party in government, populist rhetoric, including anti-intellectual rhetoric, is emasculated and approaches the “mainstream”.